Dirichlet series of GCD

n = 1 gcd ( n , 2016 ) n 2 = a b π 2 \large \sum_{n=1}^\infty \dfrac{\gcd(n,2016)}{n^2}= \dfrac{a}{b}\pi^2

If the equation above holds true for positive integers a a and b b , find a + b a+b .

Clarification :
gcd ( m , n ) \gcd(m,n) denotes the greatest common divisor of m m and n n .


The answer is 98701.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Otto Bretscher
Apr 7, 2016

That's a fun problem! Just what I needed on a slow day at the office!

If we write n = 2 a 3 b 7 c m n=2^a3^b7^cm , where gcd ( m , 2016 ) = 1 \gcd(m,2016)=1 , then the sum can be written as

( a = 0 gcd ( 2 a , 2016 ) 4 a ) ( b = 0 gcd ( 3 b , 2016 ) 9 b ) ( c = 0 gcd ( 7 c , 2016 ) 4 9 c ) ( gcd ( m , 2016 ) = 1 1 m 2 ) \left(\sum_{a=0}^{\infty}\frac{\gcd(2^a,2016)}{4^a}\right)\left(\sum_{b=0}^{\infty}\frac{\gcd(3^b,2016)}{9^b}\right)\left(\sum_{c=0}^{\infty}\frac{\gcd(7^c,2016)}{49^c}\right)\left(\sum_{\gcd(m,2016)=1}\frac{1}{m^2}\right)

This is not as bad as it looks. We know that the last term is 16 π 2 147 \frac{16\pi^2}{147} , and the others are easy to evaluate as they turn into geometric series after a few terms, for example, 1 9 0 + 3 9 1 + 9 9 2 + 9 9 3 + . . + 9 9 k + . . \frac{1}{9^0}+\frac{3}{9^1}+\frac{9}{9^2}+\frac{9}{9^3}+..+\frac{9}{9^k}+.. = 1 + 1 3 + 1 8 =1+\frac{1}{3}+\frac{1}{8} = 35 24 =\frac{35}{24} . We find

95 48 35 24 55 48 16 π 2 147 = 26125 π 2 72576 \frac{95}{48}\frac{35}{24}\frac{55}{48}\frac{16\pi^2}{147}=\frac{26125\pi^2}{72576}

and the answer is 98701 \boxed{98701} .

There are fancier ways to solve this, but why use a sledge hammer to crack a nut ;)

This is the solution i had in mind(+1)

Aareyan Manzoor - 5 years, 2 months ago

Great solution!

Muhammad Rasel Parvej - 4 years, 6 months ago
Mark Hennings
Apr 9, 2016

Indeed, a nice problem. We can generalize Otto's solution as follows: Note that a 0 p m i n ( a , n ) p 2 a = a = 0 n 1 p a + a n p n 2 a = 1 + p 1 p n 1 1 p 2 \sum_{a \ge 0} \frac{p^{\mathrm{min}(a,n)}}{p^{2a}} \; = \; \displaystyle \sum_{a=0}^{n-1}p^{-a} + \sum_{a \ge n} p^{n-2a} \; = \; \displaystyle \frac{1+ p^{-1} - p^{-n-1}}{1 - p^{-2}} for any prime p p and integer n 1 n \ge 1 . If k N k \in \mathbb{N} has prime factorization k = p 1 a 1 p 2 a 2 p m a m k\,=\, p_1^{a_1} p_2^{a_2} \cdots p_m^{a_m} , then n 1 g c d ( n , k ) n 2 = j = 1 m ( a 0 p j m i n ( a , a j ) p j 2 a ) g c d ( n , k ) = 1 1 n 2 \sum_{n \ge 1} \frac{\mathrm{gcd}(n,k)}{n^2} \; = \; \prod_{j=1}^m \left(\sum_{a \ge 0} \frac{p_j^{\mathrm{min}(a,a_j)}}{p_j^{2a}}\right) \sum_{\mathrm{gcd}(n,k) = 1} \frac{1}{n^2} and hence n 1 g c d ( n , k ) n 2 = j = 1 m 1 + p j 1 p j a j 1 1 p j 2 g c d ( n , k ) = 1 1 n 2 = j = 1 m 1 + p j 1 p j a j 1 1 p j 2 × j = 1 m ( 1 p j 2 ) ζ ( 2 ) = ζ ( 2 ) j = 1 m ( 1 + p j 1 p j a j 1 ) \begin{array}{rcl} \displaystyle \sum_{n \ge 1} \frac{\mathrm{gcd}(n,k)}{n^2} & = & \displaystyle \prod_{j=1}^m \frac{1 + p_j^{-1} - p_j^{-a_j-1}}{1 - p_j^{-2}} \sum_{\mathrm{gcd}(n,k)=1} \frac{1}{n^2} \\ & = & \displaystyle \prod_{j=1}^m \frac{1 + p_j^{-1} - p_j^{-a_j-1}}{1 - p_j^{-2}} \times \prod_{j=1}^m \big(1 - p_j^{-2}\big) \zeta(2) \\ & = & \displaystyle \zeta(2) \prod_{j=1}^m\big(1 + p_j^{-1} - p_j^{-a_j-1}\big) \end{array} giving the sum 26125 72576 π 2 \tfrac{26125}{72576}\pi^2 , and the answer 98701 \boxed{98701} , when k = 2016 k = 2016 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...